Development of National University Web-Based Digital Library Information System - Trisni Susiyanti; Dr. Fauziah; Ira Diana Solihati (Jurnal Mantik, 2020)
Management (SCM) is planning, organizing, coordinating and controlling all supply chain activities. Supply Chain Management prioritizes the flow of goods between companies from upstream to downstream (from company to shop) and involves suppliers to customers. This Supply Chain Management will provide capabilities regarding the importance of managing the supply chain in creating an efficient and effective manufacturing system, as well as systematic procedures for managing various activities in order to obtain a transformation so that it becomes a product in process, then becomes a finished product and is forwarded by delivery to consumers through the system distribution. This supply chain management aims to provide sufficient knowledge about SCM and its components, and has the ability to analyze SCM components related to the use of information technology implementation. Supply Chain is the management of various activities in order to obtain raw materials, followed by transformation activities so that they become products in the process, then become finished products and continue with delivery to consumers through the distribution system.